PERANAN PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANGAN DALAM MENUNJANG EFEKTIVITAS PENGELOLAAN PERSEDIAAN BARANG DAGANGAN (STUDI PRAKTIK KERJA PADA KOPERASI KARYAWAN SAMPOERNA) - ., SOEGIONO (: 2303-1719)
Inventory is one of the most important asset owned by a company which is engaged in trade. Because inventory is an important asset that the company must do a good internal control to keep the inventory of the risk of fraud or negligence that may have occurred. The purpose of this study was to determine the system of internal control has been implemented in the Cooperative Employees Sampoerna especially in merchandise inventory. And to know the effectiveness of the implementation of internal control systems in the inventory of merchandise at Sampoerna Employees Cooperative. Sampoerna Employees Cooperative (PRIMER) in Surabaya is engaged in the trade still has a few weaknesses in internal control process cycle of buying and selling merchandise. One of them is the absence of CCTV that is installed on a warehouse inventory merchandise. The firm also serves to let the employees work in process receipts and merchandise.